Light, but Not Nutrients, Drives Seasonal Congruence of Taxonomic and Functional Diversity of Phytoplankton in a Eutrophic Highland Lake in China - Wang, Huan; Zhao, Dandan; Chen, Liang; Giesy, John P.; Zhang, Weizhen; Yuan, Changbo; Ni, Leyi; Shen, Hong; Xie, Ping (Frontiers in Plant Science, 2020)
Information on temporal dynamics of phytoplankton communities and their responses to environmental factors can provide insights into mechanisms driving succession of phytoplankton communities that is useful in programs to manage and or remediate undesirable assemblages. Populations of phytoplankton can be controlled by bottom-up factors such as nutrients and temperature or top-down such as predation by zooplankton. Traditionally, taxonomic diversity based on morphologies has been the measure used for analysis of responses to environmental factors. Recently, according to functional groupings, including functional groups (FG), morpho-functional groups (MFG), and morphology-based functional groups (MBFG), functional diversity has been used to represent functional aspects of phytoplankton communities. However, to what extent these taxonomic and functional groupings are congruent at seasonal time-scales and the main environmental factors, which drive succession, have remained less studied. Here, we analyzed absolute and relative proportions of a phytoplankton community during a 3-year period in Lake Erhai, a eutrophic highland lake in China. Alpha diversity and beta diversity, as measured by Shannon-Wiener and Bray-Curtis indices of taxonomic grouping and three functional groupings (FG, MFG, and MBFG) were applied to investigate environmental factors determining diversity. Significant, positive relationships were observed between taxonomic diversity and functional diversity that were strongly linked through seasons. Considering that the tolerance of dominant species to some extreme conditions affected associations, when dominant species were excluded, residual communities still exhibited similar patterns of succession. This synchronous temporal pattern was not principally driven by the dominant genera (Microcystis, Psephonema and Mougeotia). Instead, the entire phytoplankton community assemblages were important in the pattern. Most diversity indices of taxonomic and functional groupings were significantly correlated with solar irradiance, but not nutrient concentrations. Because the lake is eutrophic and there were already sufficient nutrients available, additional nutrients had little effect on seasonal taxonomic and functional diversity of phytoplankton in Lake Erhai.